Simulation and analysis of ideal low pass filter response using MATLAB - Shaikh, Muhammad Zakir; Mal, Khakoo; Kumar, Dillep; Ali, Ehsan; Chowdhry, Bhawani Shankar; Baro, Enrique Nava (Mehran University research journal of engineering and technology, 2023)
Filters are the crucial element of many modern electronic systems used in control engineering, wireless communication systems, and embedded systems designs. Filters in one form or another, are considered an important subsystem in developing communication systems. The ideal filter cannot be designed through any electronic circuit and the only way is to realize using simulations tools like MATLAB. In this paper, the simulation and analysis of the ideal low pass filter is presented. The MATLAB software is used to generate and perform analysis of the step response of ideal low-pass filter (Si function) and impulse response of ideal low-pass filter (Sinc function) in time and frequency domains. The aim of the work is to provide engineering students an easier understanding of the filter design process in an appropriate way with the help of simple programming. Where, it is easy to generate signals and analyze the ideal low pass filter response. To verify achievement of learning objectives, a survey is conducted from 45 engineering students of electronic and telecommunication which elicited students’ observations and interest in the learning process. Overall about 75% of students gave positive feedback, which indicates that such type of experimentation had a significant impact on the student academic outcomes.